The utility of internal spinal marking for intraoperative localisation: A systematic review. (May 2023) - Tan, Darius; Castle-Kirszbaum, Mendel; Mariajoseph, Frederick P.; Kow, Chien Yew; Ho, Ben; Danks, Andrew; Goldschlager, Tony; Kam, Jeremy
Highlights: Several techniques including endovascular coiling, fiducials, dye, and fixed wire were described in the literature. Overall, internal spinal marking was relatively safe with high rates of accuracy. When accounting for practicality and efficacy, fiducials may be the optimal choice. This review reveals the need for further examination of internal spinal localisation techniques. Abstract: Background: Incorrect level spinal surgery is an avoidable complication, with significant ramifications. Several pre-operative spinal marking techniques have been described to aid intraoperative localisation. Methods: A systematic search of Ovid MEDLINE, and EMBASE was performed from inception to July 2022. All publications describing cases of internal spinal marking were included for further analysis. 22 articles describing 503 patients satisfied our eligibility criteria. Results: A number of localisation techniques, including endovascular coiling (n = 16), fiducials (n = 177), dye (n = 109), needle/fixed wire (n = 199), cement (n = 4), and gadolinium tubes (n = 1) were described. The highest rates of technical success were observed with endovascular coiling, fiducials, cement and dye (100 %), and complication rates were lowest with endovascular coiling, fiducials and cement (0 %). Conclusions: Overall, internal spinal marking was effective and safe. When considering practicality and efficacy, fiducial marking appears the optimal technique, as it can be performed in the outpatient setting under local anaesthesia. This review demonstrates the need for more targeted investigation into localisation methods in spinal surgery.